Building Trust in the Digital Halal Market - Dion Satrio Nugroho; Tri Deviasari Wulan (Journal of Halal Research, Policy, and Industry, 2025)
This study aims to examine the effect of Digital Halal Marketing (DHM) on Consumer Trust (CT) by investigating the mediating roles of Social Media Engagement (SME). In the rapidly growing halal industry, digital platforms have become essential tools for communicating halal values, certification transparency, and ethical positioning. However, limited research has explored how digital halal strategies translate into consumer trust through relational mechanisms. This study employs a quantitative approach using covariance-based structural equation modeling (CB-SEM) with a sample of 250 respondents collected through structured questionnaires. The findings reveal that Digital Halal Marketing significantly influences Social Media Engagement and Brand Image. Furthermore, both Social Media Engagement and Brand Image have significant positive effects on Consumer Trust. The mediation analysis indicates partial mediation, demonstrating that trust is primarily formed through interactive engagement and favorable brand perceptions rather than direct marketing communication alone. The results suggest that halal-oriented digital strategies must prioritize transparency, interactivity, and value congruence to effectively build consumer trust. The study contributes to the integration of signaling theory and engagement theory within halal digital marketing literature and provides practical insights for managers seeking to strengthen trust in competitive digital environments.